Gabriella Vöő. Kortársunk, Mr. Poe. Felfedező utak az összegyűjtött elbeszélésekben. [Our Contemporary, Mr. Poe: Journeys of Discovery in te Collected Tales]. Budapest: Ráció kiadó, 2016. 407 pp. - Sarbu, Aladár (FOCUS: Papers in English Literary and Cultural Studies, 2016)
Edgar Allan Poe has been part of the Hungarian literary consciousness since the middle of the nineteenth century. “Three Sundays in a Week,” the first of his writings to be translated, came out in 1856 (Vadon 919), the year in which Baudelaire published his Histoires Extraordinaires par Edgar Poe, bringing the American writer to the attention not only of his countrymen but also of the wider European, including the Hungarian, public. There has since been a steady stream of translations and re-translations and a variety of translators, among whom pride of place is held by Mihály Babits, a literary classic of the last century, who, not independently of his admiration for Baudelaire, rendered quite a bookful of Poe’s tales in Hungarian. (As things go, contenders for that pride of place will probably appear one day, but that is only as it ought to be, we all stand to gain.) Our Americanists are aware of the stature Poe commands in his native land,1and treat him accordingly. Nevertheless, the prevalent view among educated readers still is that offered by Babits, for whom Poe served as the context for his portrayal of Baudelaire as a poet of decay (401-03), and by Antal Szerb, who thought the tales were unbridled imaginative projections of the psyche of their author or, when not, experiments in suspense-creation through the exploitation of an unprecedentedly keen logical faculty, eventually resulting, in the invention of the detective story (377-78).